2018
DOI: 10.1063/1.5066021
|View full text |Cite
|
Sign up to set email alerts
|

Isotropic Seebeck coefficient of aligned single-wall carbon nanotube films

Abstract: How the morphology of a macroscopic assembly of nanoobjects affects its properties is a longstanding question in nanomaterials science and engineering. Here, we examine how the thermoelectric properties of a flexible thin film of carbon nanotubes depend on macroscopic nanotube alignment. Specifically, we have investigated the anisotropy of the Seebeck coefficient of aligned and gated single-wall carbon nanotube thin films. We varied the Fermi level in a wide range, covering both the p-type and n-type regimes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 15 publications
5
46
0
Order By: Relevance
“…Besides, Ichinose et al 32 suggested that the alignment of SWCNTs led to an enhanced σ but unchanged S for the aligned metallic film (sample #5), and a PF value of around 300 μW m −1 K −2 was achieved. Similar conclusion was also drawn in the study by Fukuhara et al 33 on SWCNT film (a mixture of metallic and semiconducting SWCNTs). The testing direction was illustrated in Figure 2F and SWCNT alignment degree was evaluated by polarization‐dependent Raman spectra (Figure 2G).…”
Section: Carbon Materials As Thermoelectric Materialssupporting
confidence: 89%
See 2 more Smart Citations
“…Besides, Ichinose et al 32 suggested that the alignment of SWCNTs led to an enhanced σ but unchanged S for the aligned metallic film (sample #5), and a PF value of around 300 μW m −1 K −2 was achieved. Similar conclusion was also drawn in the study by Fukuhara et al 33 on SWCNT film (a mixture of metallic and semiconducting SWCNTs). The testing direction was illustrated in Figure 2F and SWCNT alignment degree was evaluated by polarization‐dependent Raman spectra (Figure 2G).…”
Section: Carbon Materials As Thermoelectric Materialssupporting
confidence: 89%
“…Reproduced with permission: Copyright 2018, American Institute of Physics. 33 K, S of the aligned SWNT sample before and after annealing. Reproduced with permission: Copyright 2000, American Institute of Physics 34 isotropic S according to Mott's theory.…”
Section: Effect Of Cnt Species and Alignmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to these unique properties, carbon nanotubes are regarded as emerging materials in many modern technological areas such as flexible electrodes [12][13][14] , field effect transistors [15][16][17] , thermoelectric devices [18][19][20] , and reinforced materials [8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…At the intersectional and aligned regions, the intertube interaction plays decisive roles to determine the device performance, because the intertube interaction basically causes modulation of the electronic structure of the CNTs. Although the CNT mat films and aligned CNTs can work as a conducting channel in real devices, such as multi-stage ring oscillators 24,25 and thermoelectric devices [31][32][33] , little is known about the microscopic mechanism of carrier accumulation in CNT thin films by a gate electrode. In our previous work, we predicted that field inversion occurs at the intersectional region of two CNTs under a weak electric field 34,35 .…”
Section: Introductionmentioning
confidence: 99%